UWB Trapezoidal Antenna with a Band-Notch Characteristic - Noor Zirwatul Ainee, Naharuddin; Nurul Hazlina, Noordin (IEEE, 2015)
This paper presents the analysis of CPW-fed trapezoidal monopole antenna added with parasitic elements and slot. The U slot applied on trapezoidal patch to investigate the effects of slot geometrical altering to the notch and operation frequency.